Wheat Yield Gap Analysis: Productivity Enhancement Practices and Factor Level Categorizations - Muhammad Islam (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
The demand for wheat is rising rapidly to sustain the growing population. In Pakistan, many farmers lack awareness of the optimal utilization of input factors. This study aims to determine the optimal use of these factors to enhance wheat productivity, address food security challenges and support effective policy decisions. The new concept for categorizations of agronomic factors is identified in current study as a high, medium and low loss factors to make accurate policy decisions for food sustainability. Statistical analysis is applied to 26430 crop cut experiments. The absolute and relative yield gap analysis is applied. Category-1 (major loss factors) refer to those factors, whose probability share (%) at optimum level lies in (1-25%) and these are urea (125-175) kg, DAP (100-125) kg, other fertilizers (25) kg and spray (2-3) for pest attack. The rest of the farmers are experiencing a decline in productivity. Category-II (Medium loss factors) refers those with a probability share of (26-50%) at optimum levels and these are 4 irrigations, harvesting between April 1st and 20th and certified seed (26.06%). Category-III (Minor loss factors) includes factors with a probability share of 51% or above at optimum levels such as November planting and soil type. A rise in the probability ratio of area share for categories I to III at their optimum levels results in enhancement in wheat productivity in diminishing order.